Power converter comparison for solar system realization - Poh, Hwee Meng. (2013)
Solar radiation represents the largest energy flow entering the terrestrial ecosystem. After reflection and absorption in the atmosphere, some 100,000TW hit the surface of Earth and undergo conversion to all forms of energy used by humans. This resource is enormous and corresponds to almost 6,000 fold the current global consumption of primary energy (13.7TW). Thus, solar energy has the potential of becoming a major component of a sustainable energy portfolio with constrained greenhouse gas